Digital Light Microscopy of Macroporous Ceramics Processed by Consolidation Casting with Mixtures of Native Starches - Cruz, Tessie G. [UNESP]; Hein, Luis Rogerio de Oliveira [UNESP]; de Siqueira, Rafael Humberto M. [UNESP]; de Carvalho, Kelly Cristina C. [UNESP] (Carl Hanser Verlag, 2008)
Porosity in starch consolidation casting technique is rightly related to original size and morphology of starch granules, leaving a pore structure after burning out. This work reports the results for the addition of different native potato and corn starch proportions in suspension,; with TiO(2) (rutile) powder. Gelling temperature have been defined after observation under light microscopy using a heating stage. Analysis of porous network and isolated pores have been clone from images of samples surfaces obtained by depth from focus reconstruction, revealing a qualitative correlation of pores characteristics and starches additions in suspensions, suggesting that the presence of isolated or interconnected pores can be handled by starches selection to control the amylopectin and amylose contents in slurries. Also, the analysis of porous fraction distribution shows no consistent pattern through specimens' volume according to starches in mixtures.